Evaluating Asymmetric Impacts of Islamic Bank Financing on Employment In Indonesia - Cahyono, Eko Fajar; Wan Ngah, Wan Azman Saini; Law, Siong Hok; Mazlan, Nur Syazwani; Ahmad, Mohd Naseem Niaz; Mohhammed, Azali (Faculty of Economic and Business, 2025)
Research Originality: This research examines the asymmetric impact of Islamic bank financing on employment in IndonesiaResearch Objectives:. This research aims to test the nolinear impact (gn) of Islamic bank financing on employment in IndonesiaResearch Methods: This research utilizes secondary data from 2006 to 2022 and employs non-linear ARDL (Auto Regressive Distributive Lag) and Conditional ECM (Error Correction Model) analysis methodsEmpirical Results: In the short term, increases in Islamic bank financing significantly boost labor force participation (LFPR), while decreases have no significant effects. Long-term analysis shows positive changes continue to enhance LFPR, but negative changes do not impact GDP. The impact of financing on LFPR is symmetrical over time, indicating short-term asymmetries do not persistImplications: This research implies that the Indonesian government can boost the growth of Islamic bank financing to increase employment opportunities for the population both in the short and long term.JEL Classification: E24, G21,C32How to Cite:Cahyono, E. F., Ngah, W. A. S. W., Law, S. H., Mazlan, N. S., Ahmad, M. N. N., & Mohhamed, A. (2025). Evaluating Asymmetric Impacts of Islamic Bank Financing on Employment in Indonesia. Etikonomi, 24(1), 31 – 52. https://doi.org/10.15408/etk.v24i1.40139.